Pengembangan Sistem Rental Kamera Online - Ridho Saputra; Agus Wahyu Widodo; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Nowadays technological developments are progressing very rapidly. Gadgets as a facility and means of communication and entertainment are also experiencing tremendous growth. Indonesian society increasingly wants to know closer to internet technology, many who use the internet as a field of business, one of which is a site that sells or leases goods online. Not just smartphones or Tablet PCs, the camera now has a growing technology. In the development of all these technologies are also accompanied by technological developments in the field of photography, such as single lens reflect digital camera or more we are familiar with the name of DSLR cameras. The process of analysis of the validation test results is done by looking at the conformity between the results of system performance with a list of needs. Based on the results of validation testing can be concluded that the implementation and functionality of Online Camera System has met the needs that have been described in the needs analysis phase. The process of analysis of the performance test results is done by analyzing the results of testing of Online Camera Rental System.